An industry survey of the screw press system in palm oil mills: Operational data and malfunction issues. (August 2015) - Harun, M.Y.; Che Yunus, M.A.; Morad, N.A.; Ismail, M.H.S.
Highlights: Industry survey on palm oil screw press machine and its malfunction issue. 105 questionnaire were returned (response rate = 25%). The type and number of screw press employed dictates the mill's operational capacity. Double-screw press experienced earlier malfunction than single-screw press. Irregular maintenance and poor handling is the primary cause for machine failure. Abstract: Research questionnaires were disseminated to active palm oil mills across Malaysia to acquire information on (i) the mill operation, and (ii) any malfunction issues concerning the screw press system. A total of 105 mills responded to the survey (response rate = 25%). The relationship between the mill operational data (processing capacity, daily operation cycle), the screw press system (type, quantity), and the malfunction frequency was examined. The double screw press machine dominated the palm oil milling industries due to its larger capacity that entails a shorter processing time in comparison with the single screw press. Recurring malfunction problems were prevalent in both types of screw press system. While fatigue, corrosion, wear and tear are inevitable due to the heavy usage and natural causes, an irregular maintenance schedule and poor handling topped the list of common cause for malfunction of the screw press.